Effectiveness of Endophytic Bacteria from Local Tomato Plants Against Wilt Disease Caused by Fusarium oxysporum - Ratna Umi Nurlila; Jumarddin La Fua; Muhammad Sainal Abidin; Sulaeha Sulaeha; Lodes Hadju (Universitas Sebelas Maret, 2023)
Fusarium wilt is a plant disease caused by Fusarium oxysporum that generates significant economic loss to crops. A method to sustainably control F. oxysporum is utilizing biological agents, such as endophytic bacteria. Therefore, this study aimed to isolate endophytic bacteria from tomato plant tissue, which could inhibit the pathogen of wilt disease (F. oxysporum). Endophytic bacteria were isolated from local tomato plants in Muna Regency, Indonesia. Morphological characteristics such as size, shape, color and height of bacterial colonies were then determined by Gram staining using potassium hydroxide (KOH). Endophytic bacterial isolates were evaluated for their ability to inhibit F. oxysporum through inhibition and hydrogen cyanide (HCN) production tests. Subsequently, analysis of variance was used to determine whether endophytic bacteria inhibited F. oxysporum growth, and if there was a significant effect, Duncan's test was conducted at 95% significance. HCN production was observed through qualitative methods. The results showed that four endophytic bacteria isolates, namely LBR I A03, SWR II B04, SDM II B05 and SWR I A02 inhibited the growth of F. oxysporum by more than 50%. It also revealed that four endophytic bacterial isolates were strong HCN producers and two were weak producers. Therefore, isolates showing antifungal activity in this study can be used as biopesticide agents to induce plant resistance to F. oxysporum.